2018
DOI: 10.7759/cureus.3418
|View full text |Cite
|
Sign up to set email alerts
|

Review of Socioeconomic Disparities in Lower Extremity Amputations: A Continuing Healthcare Problem in the United States

Abstract: Lower extremity amputation is one of the most unfortunate, yet preventable, consequences of uncontrolled lower limb ischemia occurring secondary to diabetes mellitus or peripheral arterial disease. In the United States, racial and socioeconomic disparities are associated with significant differences seen in the incidence and type or level of lower extremity amputation among patients. Due to shifting demographics and the uncertain state of healthcare coverage, lower extremity amputation rates are only projected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Diabetic ulcers, or chronic wounds, in lower extremities can lead to incapacitation, limb loss, and unsatisfactory healing. 13 Current clinical treatments such as antibiotics, hyperbaric oxygen therapy, and moist dressings fail to attain desired healing of diabetic wounds. 14 MSCs have been shown to promote wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic ulcers, or chronic wounds, in lower extremities can lead to incapacitation, limb loss, and unsatisfactory healing. 13 Current clinical treatments such as antibiotics, hyperbaric oxygen therapy, and moist dressings fail to attain desired healing of diabetic wounds. 14 MSCs have been shown to promote wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Lower extremity amputation due to a chronic wound is a preventable consequence of peripheral vascular disease and diabetes. 1 In the diabetic population, a new onset diabetic foot ulcer has an associated mortality rate between 43% and 55% and rises to 75% after amputation. 2 4 When amputation occurs, data suggest that there is an exacerbation of existing comorbidities, rather than a new disease process, which results in increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Goodney et al reported an amputation rate of more than 23 per 10,000 Medicare patients with the peripheral arterial disease (PAD) in Florence, South Carolina [6]. Certain factors, such as age, gender, race, co-existing diseases, smoking, and socioeconomic status, among others, have been associated with higher rates of amputation [6,[8][9][10][11][12]. For example, Ciocan et al identified age as a risk factor for amputation [8].…”
Section: Introductionmentioning
confidence: 99%